Microwave and Millimeter-Wave Plasma Formation Within 2D Photonic Crystal Defects - Parsons, Stephen. (2017)
Abstract: Photonic crystals with integrated plasma elements have received increased attention in recent years due to the variable nature of their dielectric properties. To date, all such devices have included plasma elements that have been controlled using external power sources, most commonly, DC discharge tubes. Recent modeling work by Gregório et al. suggest that an electromagnetic wave incident on a photonic crystal with a central point-defect vacancy enables self-initiated gas breakdown. The vacancy left by the point-defect creates a high-Q resonant cavity which enhances the electric field within the cavity to the point of gas breakdown. Once breakdown occurs, the plasma is also maintained within the vacancy by the incoming wave. In this thesis, I will explore the environmental variables (gas pressure, input power) that allow for a plasma to be formed and sustained, and the effect the plasma has on the incoming and outgoing electromagnetic wave. Design parameters and experimental results of two photonic crystal devices are included, one in the microwave frequency regime (~8.5 GHz) and one in the millimeter-wave regime (~43 GHz). I demonstrate that self-initiation of a plasma within the central vacancy is possible in 10 Torr of argon with as little as 1.4 W for the microwave device and 40 Torr of argon and 1.5 Watts for the millimeter-wave device. Once formed, the plasma filled cavity alters the transmission properties of the photonic crystal device, reducing transmission by up to 30 dB depending on gas pressure and power. Time domain measurements of plasma formation within the microwave device reveal formation times 100 ns at 5 Torr and 9W and up to 3.5 µs at 50 Torr and 4 W. Plasma formation time for the millimeter-wave device is as low as 180 ns at 400 Torr and as high as 800 ns at 45 Torr. Using transmission of energy through the photonic crystal as a diagnostic tool, electron densities of 1016 to 1017 m-3 are measured for the microwave device and 1018 to 1020 m-3 for the millimeter-wave device.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Electrical Engineering.; Advisor: Jeffrey Hopwood.; Committee: Thomas Vandervelde, Alan Hoskinson, and Robert White.; Keywords: Plasma physics, Electromagnetics, and Electrical engineering.